Formulasi Hand & Body Lotion dengan Minyak Biji Tomat (Solanum lycopersicum L.): Studi Inovatif Pelembab dan Antioksidan untuk Perawatan Kulit - Suryani, Arman; Wahyuni, Tri (Sultan Agung Islamic University of Semarang, 2025)
Background: Exposure to free radicals can cause premature ageing, dryness, and damage to the skin. Tomato seed oil (Solanum lycopersicum L.) contains antioxidants, such as lycopene and essential fatty acids, potentially protecting the skin from oxidative stress. This study aims to develop a hand & body lotion formulation made from tomato seed oil as an innovation in skin care. Methods: This study was experimental and conducted by testing lotion formulations containing tomato seed oil. The products were tested using various parameters, including organoleptic test, homogeneity, viscosity, pH, adhesion, spreadability, antioxidant activity, and moisture. Results: The formulated hand & body lotion has a white colour, rose oil aroma, and thick texture. The homogeneity test showed consistent results, indicating a stable formulation. The lotion had a viscosity of 3408.7 ± 6.3 Cp, pH of 5.7 ± 0.2, spreadability of 15.1 ± 1.0 cm, and stickiness of 4.1 ± 0.1 seconds. The antioxidant activity IC50 was recorded at 18.03 ppm, and the treatment proved to significantly increase moisture, with significant differences on days 0, 3, and 7 (p<0.001), indicating the effectiveness and stability of the effect. Conclusion: Tomato seed oil-based hand & body lotion shows potential as an innovative product with antioxidant and moisturizing benefits. This formulation has good physical characteristics, maintains stability, is safe to use, and is well accepted.